PERANAN POLA HIDUP SEHAT TERHADAP TINGKAT KEBUGARAN JASMANI ATLET BOLA VOLI SMA INSAN CENDEKIA SYECH YUSUF KAB. GOWA - Nurul Musfira A; Arviandi Marsuki; Reza Mahyuddin (Universitas Negeri Makassar, 2023)
The life of modern society is busy every day with work, going to work in the morning and coming home in the afternoon, even late at night. In addition, they usually pay little attention to eating and physical activity, even though most of the work in the office is done sitting down, so that the person is physically inactive. Gowa Regency, this study used a descriptive research method which is a method for examining the status of human groups, an object, a set of conditions, a system of thought, or a class of events at the present time. This research was carried out in Kab. Gowa. The collection of physical fitness data is carried out using a standardized test, namely the Indonesian Physical Fitness Test (TKJI). TKJI is divided into 4 age groups, namely: 6-9 years, 10-12 years, 13-15 years, and 16-19 years. In this study, the research subjects were Insan Cendekia SMA, totaling 20 people. The instruments used in this study were to measure a healthy lifestyle and measure the level of physical fitness of Gowa Cendekiawan High School students. The number of players in each rating category obtained by players is very good 0%, good 25%, enough 55%, less 20% and very less 0%. Based on the results of the normality analysis, it can be seen that the normality test data is normally distributed. This is evidenced by the Kolmogorov-Smirnov sig value greater than α = 0.05 (0.279 > 0.05) and the Shapiro-Wilk Sig value greater than α = 0.05 (0.807 > 0.05. If if the Sig value is less than α=0.05 then the data is not normally distributed whereas if the Sig value is greater than the value α=0.05 then the data is normally distributed.The results of a healthy lifestyle survey are that the category is always in accordance with a healthy lifestyle 0% , often 95%, sometimes 5% and never 0%.The results of the correlation value of the relationship between a healthy lifestyle and the level of physical fitness is 0.126, meaning that the level of the relationship is quite close.With the results of the analysis above, there is a relationship between a healthy lifestyle and a level of fitness physical high school scholars, Gowa regency.